Performance of Glasses Containing Titan as Potential Corrosion Inhibitors for Mild Steel in a 3% NaCl Solution - Shaim,A. (2023)
Abstract Inhibition of MS corrosion in a 3% NaCl solution, by glasses containing Ti-0, Ti-5 and Ti-7, in different C, was investigated using AFM, EIS, FTIR spectroscopy, PPD, SEM and XRD techniques. PPD and IES gave IE(%) of 92.8, 99 and 98.3%, and 91.9, 98 and 98.3%, for Ti-0, Ti-5 and Ti-7 glasses, respectively, at optimum C (0.4 g/L). In addition, EIS results indicated that IE(%)increased with higher C of Ti in the glasses, reaching its maximum at 7% TiO2. The three studied compounds acted as anodic inhibitors, though anodic reactions were more suppressed than the cathodic ones. SEM revealed that the inhibitors significantly stopped the attack by Cl- ions, through chemical adsorption onto the MS surface.